115k views
4 votes
What is
(2 {x}^(2) - 7x + 6)divided by
(x - 2)

1 Answer

4 votes
Step-by-step explanation

Factoring by grouping the numerator

Step 1: We rewrite the middle terms as a sum of two terms whose product is a·c = 2·6 = 12 and whose sum is b = -7.


2x^2-7x+6=2x^2-3x-4x+6

Step 2 We group the first two terms and last two terms.


2x^2-7x+6=(2x^2-3x)-4x+6

Step 3: We factor out the greatest common factor from each group.


2x^2-7x+6=x(2x-3)-2(2x-3)

Step 4: We factor the polynomial by factoring out the greatest common factor, 2x - 3.


2x^2-7x+6=(2x-3)(x-2)

Simplifying the expression

We cancel the common factor.


\begin{gathered} (2x^2-7x+6)/(x-2)=((2x-3)(x-2))/(x-2) \\ (2x^2-7x+6)/(x-2)=2x-3 \end{gathered}Answer
2x-3

User Fuad All
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.